BUILDING TRUST TO PROMOTE AUTONOMOUS LEARNING: A CASE STUDY OF ESP INSTRUCTION IN AN INDONESIAN UNIVERSITY - Tersta, Friscilla Wulan; Karea, Syahrial; Mukminin, Amirul; Ibbara, Florante (Linguists : Journal of Linguistics and Language Teaching, 2025)
English proficiency is a crucial skill in today’s globalized world; however, non-English major students at universities often receive only two credits of English courses, which is insufficient to ensure their language mastery. This limitation presents a significant challenge for both students and lecturers, requiring innovative approaches to enhance students' learning experiences. One such approach is autonomous learning, which emphasizes students’ responsibility and self-direction in the learning process. This study aims to explore lecturers' understanding of autonomous learning and how they implement it within the constraints of limited English instruction. A qualitative research design employing a case study approach was utilized. Data were collected through semi-structured interviews with 14 lecturers teaching English in non-English study programs at a public university in Jambi, Indonesia. The participants included lecturers with varied backgrounds in English language teaching, providing diverse perspectives on the implementation of autonomous learning. The findings reveal that despite the emphasis on autonomy, students still require an instructor’s presence (teaching presence) to stimulate engagement and provide guidance in learning English. Two key themes emerged from the analysis: students’ sovereignty and trust in students’ exertion. Students' sovereignty refers to their freedom, independence, responsibility, and self-determination in identifying their learning needs and strategies. Meanwhile, trust in students' exertion highlights the importance of creating an atmosphere of acceptance, where students feel encouraged to take charge of their learning. This study underscores the need for a balanced approach between autonomy and instructional support to optimize English language learning. It is recommended that future research examine both lecturers’ and students’ perspectives to ensure that autonomous learning is a collaborative process rather than a unilateral expectation. Insights from this study contribute to the development of effective pedagogical strategies for promoting learner autonomy in higher education.